PSM UMPSA Lights Up Hari TVET Negara 2024 with Hands On Data Analytics Activities - Ku Muhammad Naim, Ku Khalif (Pusat Sains Matematik (PSM), 2024)
PSM UMPSA conducted an educational and entertaining event on “TVET in the Age of Data Analytics: Building a Future-Ready Workforce” for the Hari TVET Negara 2024 programme. It was held on 1st and 2nd June 2024, at the Mathematics Support Centre, UMPSA Gambang campus.